THE MANAGEMENT RATE OF INDIVIDUAL CONSUMPTION OF THE RESOURCE TRANSPORTER CAR - Trietiakov, A. V.; Vasiliev, O. V. (Science and Transport Progress, 2004)
The article presents a mechanism to prolong service life of flat cars (including the unique transporter flat cars) using the simulation – expertise – statistic method of managing the individual life cycle. Recommendations to decrease the utilization rate of TK-8 transporter are formulated.